Repair of Sternal Cleft in Children - BOSTANCI, KORKUT (SPRINGER, 2018)
Purpose of Review The goal of this paper is to review the surgical techniques for the correction of sternal cleft in children. Recent Findings Various surgical techniques have been developed for the correction of sternal cleft since 1949, when the first successful repair was reported. Summary Sternal cleft is an uncommon congenital chest wall deformity. The optimal correction can be achieved by primary repair of the defect in patients younger than 1 year of age, especially during the neonatal period, mostly with an easy technique. In older children, more extensive techniques are applied, using either autologous tissues or synthetic prosthetic materials, with satisfactory functional and aesthetic results.
Keywords: Sternal cleft; Sternal fissure; Surgical repair; Chest wall; CONGENITAL BIFID STERNUM; FLAPS; PENTALOGY; INFANCY; PLATE